Tinjauan Yuridis Mengenai Hak dan Kewajiban Notaris dalam Pembuatan Akta Otentik - Puspa Anggraini; Aju Putrijanti (LPPM Universitas Ekasakti Padang, 2023)
If signed in front of a notary, an authentic deed is a letter in a format determined by law and can be used as evidence that is flawless. The notary concerned must assume full responsibility for the situation if there is a problem with the deed he signed, whether it is related to civil, criminal, UUJN, or code of ethics issues. The notary will be released from this obligation if he has resigned from his job. The purpose of this study is to discuss and examine the obligations of a notary in making authentic deeds and to clarify what these rights are. Descriptive research combined with normative legal analysis methods. The notary can still be held accountable even though his term of office has ended or after the notary retires if an original deed drawn up before a notary turns out to be invalid and is detrimental to the parties.